Identifying risk factors contributing to the development of shoulder pain and injury in male, adolescent water polo players - Jameson,Yale (Division of Exercise Science and Sports Medicine, 2022)
Water polo is a fast-growing adolescent sport that consists of swimming, defending and overhead shooting in an aquatic environment. The high demands on the shoulder to complete these tasks are proposed to cause the high injury incidence reported in the sport. The novelty of this research rests in its clinically valuable contribution to understanding shoulder injury aetiology in adolescent water polo players as overhead throwing athletes. The overall research aim of this thesis explores the musculoskeletal profile of a male adolescent water polo players shoulder and the intrinsic factors associated with shoulder injury risk. An overview of the literature (Chapter 2) explores the biomechanics of water polo including swimming and overhead throwing; the musculoskeletal adaptations of overhead throwing in water polo compared to other overhead sports; and the epidemiology of shoulder injury in water polo players relative to other overhead sports. Due to the absence of a consensus-based definition of injury in water polo comparison of existing quality epidemiological studies in the sport was limited. Additionally, although a limited amount of studies have proposed potential risk factors to shoulder injury in water polo players, significant correlations are yet to be found. As with other overhead sports, the water polo shoulder is prone to injury due to the generation of high force during a modified upright swimming posture, repetitive swimming stroke and overhead throwing at high velocities. Male adolescent water polo players were recruited for this study. Chapter 3 describes the adolescent water polo player's shoulder musculoskeletal profile and its association with shoulder injury prevalence throughout a single water polo season. The musculoskeletal variables included pain provocation, range of motion, strength, flexibility and shoulder stability tests which have been used previously in overhead athletes to investigate injury prevention and performance. There were three steps in the data collection process. Firstly, informed consent and assent, demographic, competition, training and injury history, and a shoulder-specific functional questionnaire was acquired from participants. Secondly, a battery of pre-season musculoskeletal tests was performed. The battery of tests included: anthropometry, pain-provocation, glenohumeral and upward scapula range of motion, glenohumeral and scapula muscle strength, glenohumeral flexibility and shoulder stability measurements. Thirdly, at the end of the season participants completed an injury report and training load questionnaire. Participants who experienced shoulder pain, with or without medical management, were categorised into the injury group and those who did not were categorised as uninjured. Chapter 3 documents the adolescent water polo players shoulder musculoskeletal profile, shoulder injury prevalence and the association between these intrinsic risk factors and injury. Specifically, adolescent water polo players present with significant side-to-side asymmetry in the lower trapezius (p = 0.01), upward scapula rotation ROM at 90° glenohumeral elevation (p = 0.03), glenohumeral internal and external rotation ROM (p = 0.01), glenohumeral internal and external strength (p = 0.05 and p = 0.01 respectively) and the pectoralis minor index (p = 0.01). Twenty-four participants (49%) sustained a shoulder injury during the season with the dominant shoulder more commonly affected (54.2%). The most common aggravating factors were identified as throwing (41.7%) and shooting (20.8%). Although significantly lower scores on the pre-season shoulder-specific functional questionnaire (p = 0.01) and significantly greater upward scapula rotation at 90° glenohumeral elevation (p = 0.01) on the dominant shoulder was found in the injured group compared to the uninjured group, no factors were significantly associated with increased injury risk. In conclusion, the findings suggest that male adolescent water polo players are a high-risk population for shoulder injury. It is suggested that improving the players, coaches and parents' health literacy, particularly of the shoulder, and incorporating preventative exercises, targeting modifiable risk factors and side-to-side asymmetry, into pre-season conditioning programmes may reduce the prevalence of shoulder injury in this sporting population. While this research contributes to the epidemiology of shoulder injuries in water polo players, further research is needed to continue to report on injury incidence and associated risk factors, particularly training and workload characteristics in the water polo population.